Reading comprehension performance of elementary and senior high school students - de Oliveira, Adriana Marques; Santos, Jair Lício Ferreira; Capellini, Simone Aparecida (Frontiers in Education, 2023)
The aim of this study was to characterize the performance of elementary and senior high school students on semantic process tests from the Brazilian adaptation of the evaluation of reading processes (PROLEC-SE-R). A total of 436 students of both sexes, aged between 11 and 18 years, participated. The results indicated that the semantic process was equally established among high school students, with a higher average performance compared with that of elementary school students. Among elementary school students, there was progression in the average correct answers with advancement in schooling. In the two levels of education, narrative texts allowed a greater number of correct answers, followed by multiple-choice and literal questions.